SIMULASI PEMISAHAN SISTEM BINER DENGAN DISTILASI BATCH SEDERHANA - Soewarno, N; Sari, N.K; Handogo, R (Jurnal Teknik Kimia, 2006)
A simulation on separating binary system has been studied to investigate the temperature and liquid compositions profiles in the bottom changing with time. By having temperature and liquid compositions profiles in the bottom, one can find whether the binary mixture forms azeotropes or zeotropes mixtures. Antoine equation has used to calculate saturated vapour pressure at atmospheric pressure. The activity coefficient was calculated using UNIQUAC. Forward finite-difference was used to get the calculated value of the bottom still composition at a given time starting from a given initial composition of binary system. Several initial values of the composition binary system had been chosen to complete liquid compositions in the bottom. The results showed that the temperature profiles of acetone-n-butanol and ethanol-n-butanol binary system have differences characteristic from acetone-ethanol binary system. Those can be seen from activity coefficient profile. The results showed that the binary system formed zeotropes mixture, without having any azeotropes mixtures of its components. The results simulation on separation binary system has been validated with hydrocarbon binary system benzene-toluenemixture.